Intersecting epidemics: deciphering the complexities of tuberculosis-diabetes comorbidity - Araujo-Pereira, Mariana; Vinhaes, Caian L.; Barreto-Duarte, Beatriz; Villalva-Serra, Klauss; Queiroz, Artur T. L.; Andrade, Bruno B. (Frontiers in Tuberculosis, 2024)
Within the global health landscape, tuberculosis (TB) presents an ongoing challenge, demanding innovative strategies for its control. This review spotlights the intersection of TB with diabetes mellitus (DM), recognized by the World Health Organization as a key risk factor in the TB epidemic. Particularly prevalent in low and middle-income nations, the TB-DM comorbidity drives up TB rates through a nexus of chronic inflammation. By delving into the epidemiological, clinical, and inflammatory dimensions, we elucidate the impact of TB-DM on patient prognosis and the multifaceted complications it introduces to disease transmission, diagnosis, and treatment protocols. Our synthesis aims to offer a fresh lens on TB-DM, fostering a nuanced understanding that could inform future healthcare policies and interventions.